Optimizing Grazing Systems for Promoting Early Puberty in Dairy Heifers: An Integrated Nutritional Perspective - Md. Emran Hossain; Minara Begum Munni (International Journal of Biochemistry and Biomolecule Research, 2026)
The onset of puberty in dairy heifers is a critical milestone in ensuring optimal reproductive performance and overall herd productivity. Grazing systems, when strategically managed, may play a significant role in accelerating puberty through their influence on nutritional intake and heifer management practices. This review explores the impact of different grazing systems on the nutritional status of dairy heifers, emphasizing the balance between nutrient supply and demand during critical growth phases. The role of forage quality, pasture availability, and grazing management in supporting growth rates conducive to early puberty is examined. Furthermore, the interaction between grazing systems and supplemental feeding strategies is discussed to highlight how management interventions can enhance growth performance and reproductive readiness. By integrating insights from recent research on energy and protein requirements, rumen development, and metabolic signaling, this review aims to offer practical recommendations for optimizing grazing systems. The findings suggest that well-managed grazing systems, combined with targeted nutritional interventions, can effectively contribute to the timely onset of puberty in dairy heifers, supporting long-term herd health, fertility, and productivity.
Keywords: Forage; Nutrition; grazing; heifer; management